Comparison of treatment regimens to sensitize in situ hybridization for low-abundance calmodulin transcripts in the white matter of the rat spinal cord - Szigeti, Csaba (Acta Biologica Szegediensis, 2003)
We compared two in situ hybridization protocols for the detection of low-abundance calmodulin (CaM) I mRNA populations in the lipid-rich white matter of the rat lumbar spinal cord. Digoxigenin-labeled, CaM I gene-specific antisense and sense cRNA probes were used in these experiments. Although microwave heating followed by chloroform and 0.1% triton X-100 treatment resulted in the specific labeling of several cells in the gray matter of the spinal cord with a low nonspecific signal, it did not detect any CaM I expressing cells in the white matter. The protocol involving a hybridization solution adjusted to a slightly alkaline pH (pH 8.0), however, resulted in the detection of a large number of CaM-expressing cells not only in the gray matter, but also in the white matter of the spinal cord, with a nonspecific hybridization signal that was essentially identical to that of the background, and it also retained a much better overall tissue quality as compared with the protocol involving microwave heating and triton X-100 treatment. Numerous medium-sized astrocyte-like cells and smaller cells resembling oligodendrocytes were detected that expressed CaM I mRNAs throughout the white matter of the lumbar spinal cord. Thus, in situ hybridization carried out at a slightly alkaline pH is a far superior method for the detection of low-abundance mRNA populations in lipid-rich regions of the central nervous system, such as the white matter areas, as compared with microwave heating combined with triton X-100 treatment.